Proses Penyidikan terhadap Tindak Pidana Persetubuhan Terhadap Anak dibawah Umur di Polres Jember (Studi Kasus Perkara No. BP/447/XII/2011/Reskrim) - Gatot Triyanto (JURNAL RECHTENS, 2016)
Duties and authority of the police is not just become an investigator after the case occurred but will also have an important role in preventing the occurrence of felony obscenity against children, since children are so precious asset of the nation, becoming a beacon of hope for the nation's future. In connection with legal proceedings related to the process of investigation of criminal intercourse against minors are facts that the implementation process of the investigation of the crime of sexual intercourse with the accused minors are examined in the office of the Police Resort Jember has been done by the criminal procedural law, it is seen from had done investigator action procedures in conducting the investigation. Although the rights of the child suspects in the investigation process in the Police has been implemented smoothly. But on the contrary the application of the rights of children as victims of crime, has not been fully implemented. The victim if only as a witness and less attention on the state of mental trauma after giving information about the incident before investigators.